A month of summer eaudiobook Blue sky hill series, book 1. - Wingate, Lisa (Blue Sky Hills, 2008)
Lisa Wingate has been favorably compared to authors Nicholas Sparks and Richard Paul Evans. In A Month of Summer, Hanna Beth has been caring for her aging husband-who suffers from Alzheimer's-and her developmentally challenged adult son for years on her own. But when she suffers a stroke, estranged stepdaughter Rebecca must take the reins. As she cares for her father and the step-brother she's barely met, Rebecca slowly begins to heal both herself and her family.